The method of double chains for largest families with excluded subposets - Peter Burcsi; Daniel T. Nagy (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2013)
For a given finite poset P, La(n,P) denotes the largest size of a family F of subsets of [n] not containing P as a weak subposet. We exactly determine La(n,P) for infinitely many P posets. These posets are built from seven base posets using two operations. For arbitrary posets, an upper bound is given for La(n,P) depending on |P| and the size of the longest chain in P. To prove these theorems we introduce a new method, counting the intersections of F with double chains, rather than chains.